Functional characterization of the C—C chemokine-like molecules encoded by molluscum contagiosum virus types 1 and 2 - Krathwohl, Mitchell D. (The National Academy of Sciences of the USA, 1997)
Many viruses have evolved mechanisms for evading the host immune system by synthesizing proteins that interfere with the normal immune response. The poxviruses are among the most accomplished at deceiving their hosts’ immune systems. The nucleotide sequence of the genome of the human cutaneous poxvirus, molluscum contagiosum virus (MCV) type 1, was recently reported to contain a region that resembles a human chemokine. We have cloned and expressed the chemokine-like genes from MCV type 1 and the closely related MCV type 2 to determine a potential role for these proteins in the viral life cycle. In monocyte chemotaxis assays, the viral proteins have no chemotactic activity but both viral proteins block the chemotactic response to the human chemokine, macrophage inflammatory protein (MIP)-1α. Like MIP-1α, both viral proteins also inhibit the growth of human hematopoietic progenitor cells, but the viral proteins are more potent in this activity than the human chemokine. These viral chemokines antagonize the chemotactic activity of human chemokines and have an inhibitory effect on human hematopoietic progenitor cells. We hypothesize that the inhibition of chemotaxis is an immune evasion function of these proteins during molluscum contagiosum virus infection. The significance of hematopoietic progenitor cell inhibition in viral pathogenesis is uncertain.